Real life evidence Covid-19 natural infection causes more harm than Covid-19 vaccine - Ahmad Mahfuz, Gazali (CodeBlue, 2021)
A peer-review study was published in the New Journal England of Medicine on 25th August 2021, reporting the safety of the messenger RNA vaccine against SARS-CoV-2. This is one of the most significant studies in the world involving more than 800,000 vaccinated and control groups.